DESIGNING A GAME-BASED LEARNING IN PHYSICS EDUCATION USING AUGMENTED REALITY - Siti Feirusz Ahmad Fesol; Marsya Dayana Salehuddin (Journal of Islamic, Social, Economics and Development, 2022)
Physics education is considered the most complicated subject in school and servedas the basis for modern technology and tools used for research and development in science,engineering, and healthcare. However, from the survey that has been conducted among thescience stream students, there are two (2) issues that have been identified which are the studentsthink that learning Physics is difficult to understand (agreed by 73%) and learning physicsusing textbooks only is less enjoyable (agreed by 62%). To solve these, this study aims topropose a model for designing Physics education applications using the game-based learningapproach to create a more enjoyable learning environment with the assistance of theAugmented Reality (AR) element. This application employs the Rapid Application Development(RAD) methodology. The proposed solution was tested using a usability testing strategy toassess the system usability while learning Physic through game-based learning usingAugmented Reality (AR) for science stream students. The results of the study revealed that thedesigned system received an average score of 71.83% which indicates that the system has good,strong system usability in terms of its effectiveness, efficiency, and satisfaction of therespondents when using the proposed application in learning Physics. In the future, theproposed model can also be implemented in developing other subjects.